2013
DOI: 10.1007/s00231-013-1169-0
|View full text |Cite
|
Sign up to set email alerts
|

The optimum fin spacing of circular tube bank fin heat exchanger with vortex generators

Abstract: In real application, once the pattern of fin is determined, fin spacing of tube bank fin heat exchanger can be adjusted in a small region, and air flow velocity in the front of the heat exchanger is not all the same. Therefore, the effects of fin spacing on heat transfer performance of such heat exchanger are needed. This paper numerically studied the optimal fin spacing regarding the different front flow velocities of a circular tube bank fin heat exchanger with vortex generators. To screen the optimal fin sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…FaJiang et al [3] investigated the effect of pipe diameter on heat transfer rate and showed that by increasing the diameter of the pipes, the trail area behind the pipes expands and increases the heat transfer. Hu et al [4] studied increasing the distance between the fins and observed that the heat transfer remains unchanged, but the pressure drop increases. Aksenov et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FaJiang et al [3] investigated the effect of pipe diameter on heat transfer rate and showed that by increasing the diameter of the pipes, the trail area behind the pipes expands and increases the heat transfer. Hu et al [4] studied increasing the distance between the fins and observed that the heat transfer remains unchanged, but the pressure drop increases. Aksenov et.…”
Section: Introductionmentioning
confidence: 99%
“…He found that by increasing the height of the fin, the heat transfer efficiency decreased and the pressure drop increased. In a number of conducted researches, researchers have extracted from the experimental results of self-relationship work, [which include Ward-Vian 6], Maradiya et al [7], Taler [1] and Hu et al [ 4] pointed out. Numerical activities have always allocated a large share of research from the past to the present.…”
Section: Introductionmentioning
confidence: 99%
“…Hu at. all., [7] focused on a computational study the performance analysis through a rectangular channel with circular pin fins that attached to a flat surface. Staggered arrangements arranged pin fins and the heat transfer is assumed to be conjugated in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The authors developed these models by employing a GA and observed the performance of heat exchanger in relation to heat transfer and fluid flow. Several other investigators [17][18][19][20][21][22][23][24][25][26][27][28][29] used different strategies for the optimization of various heat exchangers design.…”
Section: Introductionmentioning
confidence: 99%